A tenth of an ephah of fine flour for a grain offering (Num 28,5) - Cocco, Francesco 1975- (2023)
The image that is usually associated with the sacrificial cult of the people of Israel is that of animal sacrifices, first of all the holocaust. Generally, in fact, we tend to almost completely ignore the fact that there were also vegetable offerings, which in some cases accompanied the animal sacrifice while in others represented the offer tout court in temple worship. The present work intends to study the role and function of the vegetable offering, with particular attention to the offering of "fine flour" (סֹלֶת) and its importance in the sacrificial system of the Torah in general and of the book of Numbers in particular. The study begins with a lexicographic survey, and then devotes itself to examining the occurrences of the term both in extra-liturgical and liturgical contexts.
Keywords: culto israelítico; libro de los Números; ofrenda vegetal; Sacrificio